Control of an 8L45 transmission inside the Colorado State University EcoCAR 3 2016 Chevrolet Camaro - Knackstedt, Clinton, author; Quinn, Jason, advisor; Bradley, Thomas, committee member; Marchese, Anthony, committee member (Colorado State University. Libraries, 2021)
The hybridization and electrification of vehicles brings new challenges to the engineering and development of automotive control systems. Parallel, single motor pre-transmission hybrid electric vehicles are a preferred design for hybrid vehicles because of the mechanical simplicity, in that the electric motor and engine are on a common axis, connected to the transmission. Mechanically, this configuration enables the electric motor to take advantage of the torque multiplication of the final drive gear and transmission. From a controls perspective, this configuration is complicated because the engine, motor and transmission must work together to achieve the system-level objectives of fuel economy and driveability. These challenges are exemplified in the development of the hybrid 2016 Chevy Camaro developed by the Colorado State University (CSU) EcoCAR 3 team. The results of this thesis demonstrate model development, model validation, and controls development to control the operation of the electric motor and engine together for driveability and performance during transmission gear changes. A model was developed in MATLAB Simulink to predict the behavior and performance of the 8-speed automatic transmission 8L45 that is stock to the 2016 Chevrolet Camaro. The performance of this model was validated by comparison to on-track vehicle data with <0.3m/s average error in prediction of the vehicle speed trace. A control system was developed to enable control of electric motor torque during shifts which eliminates ignition timing-based torque requests while maintaining driveability-derived shift dynamics. This work has implications for the design of automatic transmission hybrid electric vehicles with discussion focusing on the potential for integration of learning technologies and minimization of gear lash.
Keywords: automotive control systems; hybrid electric vehicles; transmission; fuel economy; driveability; EcoCAR 3D; gears